CNC Plotter Printed Circuit Board - Noor Yulita Dwi Setyaningsih; Moh Rizal; Budi Cahyo Wibowo (Jurnal Media Elektrik, 2024)
Prited Circuit Board is one part of the field of electronics that has many roles and benefits. This automatic PCB path manufacturing will provide many benefits to users that were previously still done manually. In this research, the PCB carving process will be operated using G-Code and GRBL controller to control the machine. The use of 3 stepper motors will provide a good carving composition in terms of x, y and Z axis movements, as well as the use of spindles for drill bit control that functions to carve PCB layouts. From the results, the PCB path manufacturing process is faster and has the accuracy of the specified design